The influence of personal and organizational factors on ethical decision making intentions among managers in the oil and gas companies / Zetty Zahureen Mohd Yusoff ... [et al.] - Mohd Yusoff, Zetty Zahureen; Zakaria, Zainuddin; Ali, Md Izuddin; Salleh, Wan Anisabanum (Institute of Research, Development and Commercialization (IRDC), 2005)
Ethics is attracting the attention of management in both the public and private sector organization. This paper explores an empirical assessment of the influence of job satisfaction, organizational commitment, codes of ethics and rewards, which lead managers' behaviours to their intention in making decision ethically. This paper employed the correlation tests to investigate the impact of persona; and organizational factors on ethical decision making intentions among managers and used the one-way ANOVA to determine the impact of the managers' demographic profiles towards the ethical decision making ability. The t-test analysis was used to investigate the influence of the independent sample i.e. gender towards the ethical decision making ability. The primary data were gathered between October and December 2005 by using a questionnaire, which was sent via electronic mail and post and also hand-delivered. This exploratory study found that job satisfaction, organizational commitment, codes of ethics and rewards significantly influenced ethical decision making of managers in oil and gas companies. Suprisingly, the academic qualification and salary levels were also found to significantly and highly influence the ethical decision-making ability among managers.